2021
DOI: 10.1007/s10620-020-06820-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Therapy of 3 Days May Be Sufficient After Biliary Drainage for Acute Cholangitis: A Systematic Review

Abstract: Background The optimal antibiotic therapy duration for cholangitis is unclear. Guideline recommendations vary between 4 and 14 days after biliary drainage. Clinical observations and some evidence however suggest that shorter antibiotic therapy may be sufficient. Objective To compare the effectiveness and safety of short-course therapy of ≤ 3 days with long-course therapy of ≥ 4 days after biliary drainage in cholangitis patients. Methods We searched the databases PubMed, EMBASE, Cochrane Library, and trial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Our investigation suggests that the outcomes of patients with AC with multiple hilar biliary obstructions may be poor. Although it is challenging to fully align our definition of outcomes with those of previous reports, the clinical cure rate of Group 3 was 87.1%, which is inferior when compared with those of Groups 1 and 2 or previous reports 4–6 . Unlike the simple obstruction in the bile ducts outside the liver, in cases of multiple hilar biliary obstructions, it is sometimes difficult to achieve complete drainage of the entire bile duct.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Our investigation suggests that the outcomes of patients with AC with multiple hilar biliary obstructions may be poor. Although it is challenging to fully align our definition of outcomes with those of previous reports, the clinical cure rate of Group 3 was 87.1%, which is inferior when compared with those of Groups 1 and 2 or previous reports 4–6 . Unlike the simple obstruction in the bile ducts outside the liver, in cases of multiple hilar biliary obstructions, it is sometimes difficult to achieve complete drainage of the entire bile duct.…”
Section: Discussionmentioning
confidence: 67%
“…19 We considered antimicrobial therapy duration as an important factor to investigate based on previous reports indicating that it can be shortened compared with the recommended duration in the TG18. [4][5][6] To assess the conditions of patients immediately before the discontinuation of antibiotics, we incorporated NEWS into our analysis. The United Kingdom's National Early Warning Score Development and Implementation Group developed the NEWS to assess deteriorating conditions in hospitalized patients and to predict inpatient death or intensive care unit (ICU) admission.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In acute cholangitis, the Tokyo Guidelines 2018 (TG18) recommend 4-7 days of antibiotic treatment for patients with acute cholangitis once the source of infection is controlled, but evidence for this was graded as low (evidence level C) [36]. Most studies discussed the early ERCP for acute cholangitis regarding biliary drainage only [37]. Rare studies reported the duration of antibiotics after single-stage ERCP stone removal.…”
Section: Discussionmentioning
confidence: 99%